-g+3+g=4g+7

Simple and best practice solution for -g+3+g=4g+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -g+3+g=4g+7 equation:


Simplifying
-1g + 3 + g = 4g + 7

Reorder the terms:
3 + -1g + g = 4g + 7

Combine like terms: -1g + g = 0
3 + 0 = 4g + 7
3 = 4g + 7

Reorder the terms:
3 = 7 + 4g

Solving
3 = 7 + 4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-4g' to each side of the equation.
3 + -4g = 7 + 4g + -4g

Combine like terms: 4g + -4g = 0
3 + -4g = 7 + 0
3 + -4g = 7

Add '-3' to each side of the equation.
3 + -3 + -4g = 7 + -3

Combine like terms: 3 + -3 = 0
0 + -4g = 7 + -3
-4g = 7 + -3

Combine like terms: 7 + -3 = 4
-4g = 4

Divide each side by '-4'.
g = -1

Simplifying
g = -1

See similar equations:

| 8.7/2=q/4 | | 4y=7+7+7+7 | | t-16=18 | | 3*0.166666666=a | | -2.3x-0.18=2.5x-2.2(x-1.1) | | .2(2x-8)=7 | | 7+4=18 | | 5=4m+m | | 0-6=0 | | 30.5=-9.5+6(f-8) | | -6[k-(2k+8)+6]=2(k+2) | | 180=12x+2+12x-4+12x-3 | | 4x+(x-5)=180 | | r/84=32.5/182 | | 4-19=17 | | 4+6(7c+7)= | | 4+9=57 | | c+24=36 | | 20.5=-2(3r+7) | | 2*0.166666666=a | | c+28=17 | | 7+3z=13 | | 11x^2+106x+63=0 | | -5-6.5(1+9.5x)=-26.5 | | 1.3(8-b)+3.7=-52 | | 2.4x-11.3=3.7-.6x | | 8=2x+m | | 1-15s=2(1-s) | | 2n-11=47 | | 6+6+6=3x | | x^3-32x+35=0 | | 1.05s-0.01(584.8-s)=28.26s |

Equations solver categories